2021
DOI: 10.34067/kid.0002722021
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Attenuates Organ Fibrosis via an Angiotensin Type 2 Receptor Mechanism in Aged Hypertensive Female Rats

Abstract: Background: The anti-fibrotic effects of recombinant human relaxin (RLX) in the kidney are dependent on an interaction between its cognate receptor (RXFP1) and the angiotensin type 2 receptor (AT2R) in male models of disease. Whether RLX has therapeutic effects, which are also mediated via the AT2R, in hypertensive adult and aged/reproductively senescent females is unknown. Thus, we determined whether treatment with RLX provides cardiorenal protection, via an AT2R-dependent mechanism, in adult and aged female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…Whilst it was previously only demonstrated that the HCMFs used in this study expressed RXFP1 [34], the current study further validated that RXFP1 blockade (with the B-R13/17K H2 compound) was able to annul the myofibroblast NLRP3 inflammasomeinhibitory effects of RLX (from the level of TLR-4 to pro-IL-1β and pro-IL-18). Secondly, the results obtained align with growing evidence which has pointed out that RLX-RXFP1 signalling is able to interact (or potentially undergo crosstalk) with other receptors to mediate the therapeutic effects of RLX, including the AT 2 R [27,28,33], Notch-1 [32], glucocorticoid receptor [43,44] and PPAR Υ [45,46]. Furthermore, the results obtained from the in vitro studies conducted confirmed that RXFP1-AT 2 R crosstalk played a central role in facilitating the therapeutic effects of RLX [27,28,33], which now appear to include its ability to inhibit myofibroblast NLRP3 inflammasome activity (Figure 7).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Whilst it was previously only demonstrated that the HCMFs used in this study expressed RXFP1 [34], the current study further validated that RXFP1 blockade (with the B-R13/17K H2 compound) was able to annul the myofibroblast NLRP3 inflammasomeinhibitory effects of RLX (from the level of TLR-4 to pro-IL-1β and pro-IL-18). Secondly, the results obtained align with growing evidence which has pointed out that RLX-RXFP1 signalling is able to interact (or potentially undergo crosstalk) with other receptors to mediate the therapeutic effects of RLX, including the AT 2 R [27,28,33], Notch-1 [32], glucocorticoid receptor [43,44] and PPAR Υ [45,46]. Furthermore, the results obtained from the in vitro studies conducted confirmed that RXFP1-AT 2 R crosstalk played a central role in facilitating the therapeutic effects of RLX [27,28,33], which now appear to include its ability to inhibit myofibroblast NLRP3 inflammasome activity (Figure 7).…”
Section: Discussionsupporting
confidence: 77%
“…Secondly, the results obtained align with growing evidence which has pointed out that RLX-RXFP1 signalling is able to interact (or potentially undergo crosstalk) with other receptors to mediate the therapeutic effects of RLX, including the AT 2 R [27,28,33], Notch-1 [32], glucocorticoid receptor [43,44] and PPAR Υ [45,46]. Furthermore, the results obtained from the in vitro studies conducted confirmed that RXFP1-AT 2 R crosstalk played a central role in facilitating the therapeutic effects of RLX [27,28,33], which now appear to include its ability to inhibit myofibroblast NLRP3 inflammasome activity (Figure 7).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…SHRSP are salt sensitive and if fed a high salt diet, > 95% of SHRSPs die of stroke between 6 and 12 Mo [ 16 , 22 ]. However, previous reports indicate SHRSPs, in the absence of salt loading, survive past 9Mo of age for males [ 25 , 26 ], and past 15Mo of age for females [ 27 ]. In the present study, none of the male or female SHRSPs (of which all were fed a normal sodium diet) showed signs of stroke or died spontaneously by the final timepoint of 8.5Mo of age.…”
Section: Discussionmentioning
confidence: 99%